Childhood Trauma Predicts Cancer Treatment–Related Pain in Breast Cancer Survivors. Issue 4 (July 2020) - Kanzawa-Lee, Grace A.; Knoerl, Robert; Williams, David A.; Clauw, Daniel J.; Bridges, Celia M.; Harte, Steven E.; Kolarik, Ellen; Houghtby, Janet; Lavoie Smith, Ellen M.
Abstract : Background: Childhood trauma has been linked to neuropathic pain in noncancer populations, but its relationship with cancer treatment-related neuropathic pain is unknown. Objective: This secondary data analysis of a prospective, longitudinal, observational study aimed to explore the relationship of childhood trauma experience with pain severity, pain interference, and neuropathic symptom severity (NSS) 12 months after surgery in women receiving treatment for stage 0 to III breast cancer. Methods: Women (N = 44) recruited from a comprehensive cancer center self-reported childhood trauma experience, pain severity, pain interference, NSS, co-occurring symptoms, and pain beliefs via questionnaires. Descriptive statistics were used to describe childhood trauma experience. Linear regression was used to model childhood trauma and other predictors on pain variables 12 months after surgery. Results: Childhood trauma predicted pain severity and pain interference 12 months after surgery ( P < .05), as did baseline pain severities and helplessness-pain catastrophizing. Age predicted only NSS. Together, the best models predicted 31.6% to 40.9% of the variance in pain severities at 12 months ( P < .001). Conclusions: Childhood trauma exposure was a significant predictor of pain 12 months after breast cancer surgery and adjuvant treatment. Younger and helplessness-pain catastrophizing women are also at risk. Research is needed to identify preventive neuropathic pain interventions for high-risk women. Implications for Practice: Women receiving breast cancer treatment should proactively be assessed for childhood trauma history, possibly by using discreet previsit questionnaires. Childhood trauma survivors may be at high risk for poor pain outcomes and may benefit from tailored pain interventions.